Infrasound waves and sulfur dioxide emissions caused by the 2022 Hunga volcanic eruption, Tonga - Bai, Ling; Liu, Chaoya; Ji, Yingfeng; Zhu, Weiling (Frontiers in Earth Science, 2023)
A powerful volcanic eruption that occurred in Tonga on January 15, 2022, produced strong vibrations in the atmosphere, ocean, and solid earth. We identify infrasound waves traveling with an apparent velocity of 0.31 km/s up to 10,000 km from Tonga in seismic and tsunami recordings. Clear signals of these infrasound waves with a fundamental model of Lamb wave are evident before the shallow-water gravity wave and after the Rayleigh and body waves. The pressure amplitudes of the infrasound waves at stations of 400-1000 km from the eruption are 5-10 hPa. The infrasound wave generated trans-Pacific tsunami waves to arrive 4-5 hours earlier than the gravity waves of regular tsunami in the populated countries near the Pacific oceans. We use numerical simulation methods for the oceanic plate subduction zone in Tonga to estimate the pressure-temperature fields and the desulfurization at shallow depths. The simulated total sulfur dioxide released during the eruption ranges from 0.4 to 2.0 Tg. This is small in comparison with previous studies of comparable infrasound pressures. The total emission and sulfur dioxide amounts may have been controlled by the amount of sulfur contained in the subducted plate as well as the pressure and temperature conditions of the subduction zones.